Balinese Muslim Identity Construction: Symbol of Harmonious Communication Among Religious Adherents in Indonesia - Nurdin, Ali; Novriansyah, Brenny; Ridwan, M.; Sulaeman, Sulaeman (Technium Social Sciences Journal, 2022)
The construction of identity is formed in the dialectic between the individual and society. The relationship between individuals and society produces self-identity and ego. Self-identity survives according to individual beliefs since birth, the identity of ego can facilitate as a solution to the problems that occur in the community environment. The study purposed to describe the construction of Balinese Muslim identity as a symbol of harmonious communication among religious adherents in Indonesia. This research uses descriptive-qualitative type. Data collection techniques using interviews, observation, and document review. Analysis of the data using a model of the flow through the stages of data reduction, data presentation, conclusion and verification. The findings from this study suggest that the construction of Muslim self-identity in daily life is displayed through the implementation of worship as a symbol of Muslims. Symbols of identity include the implementation of the prayer, zakah, fasting, and pilgrimage. In additions, adhan as a symbol of the implementation of the prayers, the existence the big feast of Islam, the celebration of the holiday, and as well as the wearing of hijab and hat songkok for Muslims are also symbols of Muslim identity. The construction of ego identity is represented in Islamic institutions symbolized by the existence of mosques, Islamic boarding schools, madarsa/school, and the tomb of guardian place of seven (Wali Pitu) as a site of religious tourism. The study produced a map displaying Muslim identity in everyday and institutional Islam, as well as the identity of the ego that is displayed in interrelationship with society. The construction of Balinese Muslim identity is part of the symbol of harmonious communication among religious adherents in Bali, Indonesia.